Increasing the Selling Value of Indonesian Cultural Products to the Global (Case study of Batik as Indonesian Cultural Identity): Meningkatkan Nilai Jual Produk Budaya Indonesia kepada Global (Studi Kasus Batik sebagai Identitas Budaya Indonesia) - Ferric Limano (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2021)
Culture consists of practices, objects, and values ​​in one society. This culture occurs as a result of the emergence of transactions and agreements between certain communities so as to agree on these existing values ​​into the daily life. Even this culture itself is passed down from generation to generation, the identity of this culture demands uniqueness, boundaries, and originality. But the big problem is the strong current of globalization which makes the mingled interactions between one and another culture. Indonesia is rich in culture, which in the past also experienced a lot of acculturation with one another. The uniqueness of Indonesian culture is displayed in many forms, both objects and habits, including performing arts in Bali, phinisi ships, and also batik. Through this research the authors again raise how to increase the selling value of cultural products in Indonesia, by looking at the case studies of traditional batik which innovated into a global approach. This case is discussed from the point of view of Komaruddin Kudiya's success in introducing batik to the global market. The research method was carried out qualitatively, with a cultural and business design approach. The data obtained is based on workshops and seminars, as well as literature obtained online. Furthermore, the data will be studied and analyzed descriptively to produce explanations related to the factors that increase the selling value of batik as a result of Indonesian culture.